The Role of Artificial Intelligence in the Transformation of Judicial Processes - Pulache, Gerson (2025)
This article conducts a systematic review to analyze the impact of artificial intelligence (AI) on the transformation of judicial processes, following the guidelines of the PRISMA methodology. The main objective is to assess how AI contributes to efficiency, accuracy and accessibility in the judicial field, identifying both its benefits and associated ethical challenges. Studies published between 2020 and 2024 were collected and analyzed in databases such as Scopus and SCielo, using specific search equations and previously defined inclusion and exclusion criteria. The results highlight that AI can optimize judicial processes by automating routine tasks and predictive decision making, with examples of implementation in countries such as Estonia and Singapore. However, concerns about algorithmic biases and system transparency were also identified. It is concluded that, to ensure fair and effective adoption, it is critical to establish regulatory frameworks and promote human oversight in judicial systems that integrate AI.